Evaluation of α-fetoprotein-L3 and Golgi protein 73 detection in diagnosis of hepatocellular carcinoma - Jia, Zhiling; Wang, Li; Liu, Chang; Yu, Zhonghe; Chai, Lina; Zhao, Mancang (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study : Hepatocellular carcinoma (HCC) is common throughout the world. Most HCCs are diagnosed at an advanced stage. There is an urgent need to find new methods for screening and surveillance of individuals at risk for HCC. The aim of this study was to evaluate serum α-fetoprotein (AFP)-L3 and serum Golgi protein 73 (GP73) detection in diagnosis of HCC with different AFP concentration. Material and methods: One hundred and eighty one patients were involved, including 102 with HCC and 79 with benign liver disease. The serum AFP-L3 and GP73 was measured by a liquid-phase binding assay and quantitative enzyme-linked immunosorbent assay, respectively. Results : Of the 102 HCC patients, 53 were positive for AFP, 77 were positive for AFP-L3, and 79 were positive for GP73. The maximum area under the curve for AFP-L3% and for GP73 was significantly different from the AUC of 0.5525 for total AFP (p < 0.01). AFP-L3% was not detected for AFP 400 ng/ml, AFP-L3% > 10% was present in 96.23%, and GP73 was detected in 87.50%. Conclusions : The determination of AFP-L3% and GP73 in combination with AFP can increase the sensitivity and specificity in diagnosis of HCC. α-fetoprotein-L3% and GP73, in combination with AFP, are useful biomarkers to confirm the diagnosis of HCC.